2015
DOI: 10.1097/md.0000000000001682
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Fatty Liver Index for Nonalcoholic Fatty Liver Disease in Middle-Aged and Elderly Chinese

Abstract: The fatty liver index (FLI), which is an algorithm based on waist circumference, body mass index (BMI), triglyceride, and gamma-glutamyl-transferase (GGT), was initially developed to detect fatty liver in Western countries. Our study aimed to evaluate the accuracy and optimal cut-off point of the FLI for predicting nonalcoholic fatty liver disease (NAFLD) in middle-aged and elderly Chinese.This cross-sectional study included 8626 Chinese adults aged 40 years or above recruited from Jiading District, Shanghai, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
169
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(182 citation statements)
references
References 27 publications
6
169
3
4
Order By: Relevance
“…In our household survey, the diagnosis of NAFL was based on the fatty liver index (FLI), an algorithm derived from the population of the Dionysos Nutrition and Liver Study . An optimal cut‐off value for FLI to detect fatty liver is still the subject of debate, and in a recent Chinese study, a value of 30 was shown to have better diagnostic sensitivity than a value of 60 . To avoid overestimating the NAFL population in our study, as in many others, 60 was assumed to be the discriminative point.…”
Section: Discussionmentioning
confidence: 99%
“…In our household survey, the diagnosis of NAFL was based on the fatty liver index (FLI), an algorithm derived from the population of the Dionysos Nutrition and Liver Study . An optimal cut‐off value for FLI to detect fatty liver is still the subject of debate, and in a recent Chinese study, a value of 30 was shown to have better diagnostic sensitivity than a value of 60 . To avoid overestimating the NAFL population in our study, as in many others, 60 was assumed to be the discriminative point.…”
Section: Discussionmentioning
confidence: 99%
“…The equations are described in Table S1. Serum albumin was not measured in the KNHANES; therefore, significant fibrosis was defined as either the highest quartile of the NAFLD fibrosis score, the highest quintile of Forns index, or fibrosis‐4 index ≥2.67, whereas a fatty liver index ≥30 or a comprehensive NAFLD score ≥40 was considered indicative of a fatty liver …”
Section: Methodsmentioning
confidence: 99%
“…A series of predicting indexes was developed and validated individually in Europe and Asia [10,26,27]. Few studies were conducted to appraise indexes in western China, which witnesses a variety of differences in culture, diet and lifestyle in comparison to eastern China.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty liver index (FLI) [5], the hepatic steatosis index (HSI) [6] and lipid accumulation product (LAP) [7] have been derived and utilized to screen hepatic steatosis in large epidemiologic studies or identify potential patients for further examination in clinical practice. The evaluation of the indexes' diagnostic performance has been reported in Europe [8] and Asia [9,10] over the past decade; however, external validation of them in western China is rare.…”
mentioning
confidence: 99%